(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The Tabi'in aware of the status of the hadith of the Prophet, and they knew its value, and they comprehended the texts ordering the transmission of knowledge, and they transmitted it to their successors in the best possible way. If we reflect on their books, it would be crystal clear that they have given their greatest effort in the pursuit of conserving hadith. Through it, they were able to memorize the hadith of the Messenger of God, may God bless him and grant him peace, and to pass it on to the next generations in a soft way. The researcher followed the extrapolative approach of eliciting some of the most remarkable ways, efforts and means of the companions and their followers, and found that they were using almost the same steps as the communicators - God willing - in keeping and caring for the conversations. It was the same method that was used by the Companions in their memorization of hadiths and care for them, but it clarified and developed some of these approaches; They expanded on some means and methods, such as the journey in seeking hadith, opposition and comparison between narrations; According to the necessities of time and the surrounding circumstances, this is an increase in caution and caution, and such is the collection of the chains of transmission in one hadith due to its great importance in the balance of hadith criticism. And their agreement that a hadith is not taken into account unless its narrators are described as fair and precise, and they have mastered the writing and classification of hadith and others, and these efforts have resulted in preserving hadith and spreading it among the people.